Benefit of a multimodal approach combining chemotherapy and surgery in oligometastatic gastric cancer: experience from a tertiary referral center - Maratta, Maria Grazia; Vitale, Antonio; Basso, Michele; Vivolo, Raffaella; Di Monte, Elena; Biondi, Alberto; Di Giorgio, Andrea; Rosa, Fausto; Tondolo, Vincenzo; Agnes, Annamaria; Tortora, Giampaolo; Strippoli, Antonia; et al. (Frontiers in Oncology, 2024)
Gastric cancer (GC) is the fourth cause of cancer-related death worldwide. Up to 34% of newly diagnosed gastric cancer are in advanced stage with a poor prognosis in spite of the recent advances in systemic therapy. Aim of this study was to analyze the value of adding surgery to the first-line treatment in oligometastatic (OGC) patients. This retrospective study included patients with OGC underwent induction chemotherapy followed by surgery of both primary tumor and synchronous metastasis between April 2012 and April 2022. Endpoints were Overall Survival (OS) and Relapse-free Survival (RFS) analyzed by Kaplan-Meier method. Prognostic factors were assessed with Cox model. Data from 39 patients were collected. All cases were referred to our Multidisciplinary Tumor Board (MTB) to evaluate the feasibility of radical surgery. At a median follow-up time of 33.6 months, median OS was 26.6 months and median RFS was 10.6 months. Pathologic response according to Mandard criteria, PS ECOG ≤ 1 and a low metastatic burden were related with good prognosis. A sequential strategy of preoperative chemotherapy and radical surgical excision of both primary tumor and metastases demonstrated to significantly im-prove OS and RFS. Multidisciplinary evaluation is mandatory to identify patients who could benefit from this strategy.